IDENTIFIKASI TEKNIK KONSERVASI TANAH DAN AIR DI KAWASAN PERSAWAHAN UNTUK MENUNJANG PENGEMBANGAN AGROWISATA KABUPATEN MINAHASA TENGGARA - Jubert Prima; Ir. David P. Rumambi, MS; Ir. Yani E. B. Kamagi (Universitas Sam Ratulangi, 2022)
ABSTRACTThis research aimed to: (1) identify soil and water conservation techniques used by farmers/farmer groups in therice fields of Mbhuk, Wowol, and Kinawakan; (2) identify the difficulties faced by farmers/farmer groups in adopting andapplying soil and water conservation techniques in the rice fields of Mbhuk, Wowol, and Kinawakan; and (3) assess thepotential objects and attractiveness of the rice fields of Mbhuk, Wowol, Kinawakan to be developed as an agro-tourismarea in Southeast Minahasa Regency. The sample locations (observations) were determined by following the direction ofthe transect/ path intersecting the slope. The data or information obtained during the study was classified based on theresearch purposes and analyzed using qualitative descriptive analysis. The findings revealed that: 1 (a) Land use in therice fields of Mbhuk, Wowol and Kinawakan consists of rice fields, dry land, and dry land former of rice fields; (b) Thevegetative soil and water conservation techniques identified at the study site consist of relay cropping, intercropping, covercrops, and green mulch. Meanwhile, mechanically identified are bench terraces and mounds; (2) The difficulties faced byfarmers in adopting soil and water conservation techniques influenced by education, agricultural area and land ownership,as well as access to information and observerability; (3) The total value of potential objects and tourism attractions is asmuch as 2.010 with an average value of 502,5. This value denotes that the rice fields of Mbhuk, Wowol and Kinawakanare in the criteria of potential enough to be developed as an agro-tourism destination.Keywords : Soil and water conservation, rice fields, agro-tourism